1963
DOI: 10.1063/1.1702731
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Electron Concentration of Donor-Doped GaAs Crystals Caused by Annealing

Abstract: GaAs doped with ∼1019 cm−3 Se or Te shows reversible temperature-dependent changes in electron (donor) concentration over the temperature range 650 to 1100°C. Crystals containing between 2×1018 cm−3 to approximately 1019 cm−3 donors conform to the same equilibrium curve with an enthalpy of ∼0.5 eV. The behavior is that expected for a solubility equilibrium. Evidence against an equilibrium involving donor precipitation is presented, and the suggestion that the donors may interact to form molecules is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…It is also known [5] that similar heat treatment produces large changes of free electron concentration in these materials. Here we are interested in quantitative relation between changes of free electron concentration caused by annealing and the amount of impurity atoms involved in large defects.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known [5] that similar heat treatment produces large changes of free electron concentration in these materials. Here we are interested in quantitative relation between changes of free electron concentration caused by annealing and the amount of impurity atoms involved in large defects.…”
Section: Introductionmentioning
confidence: 99%
“…It was already reported that an annealing cauSes reverSible changes of the free electron concentration in sufficiently highly doped n-GaAs [12,13]. Here similarly reversible changes of DXS are reported.…”
mentioning
confidence: 49%
“…In heavily doped GaAs:Te reversible changes of the free electron concentration with the high temperatures annealing were observed since early sixties [1,2]. Tellurium doping of GaAs is used to provide n-type conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Various hypotheses were proposed to explain this deactivation mechanism in GaAs:Te. Fuller and Wolfstirn [1] suggested creation of impurity molecules which trap electrons. Some papers indicate gallium vacancy associated with the Te As quasisubstitutional defect as responsible for the observed compensation eect [2,5,6].…”
Section: Introductionmentioning
confidence: 99%